2012
DOI: 10.1007/s10460-012-9378-6
|View full text |Cite
|
Sign up to set email alerts
|

Can public GAP standards reduce agricultural pesticide use? The case of fruit and vegetable farming in northern Thailand

Abstract: In response to the chronic overuse and misuse of pesticides in agriculture, governments in Southeast Asia have sought to improve food safety by introducing public standards of good agricultural practices (GAP). Using quantitative farm-level data from an intensive horticultural production system in northern Thailand, we test if fruit and vegetable producers who follow the public GAP standard use fewer and less hazardous pesticides than producers who do not adhere to the standard. The results show that this is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 21 publications
0
47
1
Order By: Relevance
“…They also exhibited significantly superior performance to uncertified farms in several pesticide handling items. These findings appear different from Schreinemachers et al"s (2012) study of Thailand"s Q-GAP, which found no statistically significant differences in the annual amount of pesticide use and handling between 45 certified and 245 uncertified farms for nine FFV crops in Northern Thailand.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…They also exhibited significantly superior performance to uncertified farms in several pesticide handling items. These findings appear different from Schreinemachers et al"s (2012) study of Thailand"s Q-GAP, which found no statistically significant differences in the annual amount of pesticide use and handling between 45 certified and 245 uncertified farms for nine FFV crops in Northern Thailand.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, pesticide handling practices of certified farms appear to be performed better than uncertified farms with five of the total 14 items exhibiting a statistically significant difference (p < 0.05 or p < 0.01). Although a direct comparison may not be appropriate, it should be noted that this finding parts ways with the aforementioned Schreinemachers et al (2012) on Q-GAP where no significant differences in pesticide handling were found between certified and uncertified farms for seven items 1 .…”
Section: Pesticide Handlingmentioning
confidence: 56%
See 3 more Smart Citations